2020
DOI: 10.3389/fnagi.2019.00359
|View full text |Cite|
|
Sign up to set email alerts
|

Positive Allosteric Modulation of Alpha7 Nicotinic Acetylcholine Receptors Transiently Improves Memory but Aggravates Inflammation in LPS-Treated Mice

Abstract: Neuroinflammation accompanies or even precedes the development of cognitive changes in many brain pathologies, including Alzheimer's disease. Therefore, dampening inflammatory reactions within the brain is a promising strategy for supporting cognitive functions in elderly people and for preventing the development of neurodegenerative disorders. Nicotinic acetylcholine receptors containing α7 subunits (α7 nAChRs) are involved in regulating cell survival, inflammation, and memory. The aim of our study was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…These studies pushed us to search the approaches to overcome the pathological effects of neuroinflammation and α7 nAChR deficiency. In particular, it was shown that neuroinflammation can be prevented or even cured by activating α7 nAChRs with orthosteric agonist [36] or by up-regulating alternative nAChR subtypes with the growth factors produced by mesenchymal stem cells [37]. One of our previous papers described the efficiency of NSE to prevent neuroinflammation in the wild-type mice either treated with LPS of immunized with α7 nAChR extracellular domain 1-208 [22].…”
Section: Discussionmentioning
confidence: 99%
“…These studies pushed us to search the approaches to overcome the pathological effects of neuroinflammation and α7 nAChR deficiency. In particular, it was shown that neuroinflammation can be prevented or even cured by activating α7 nAChRs with orthosteric agonist [36] or by up-regulating alternative nAChR subtypes with the growth factors produced by mesenchymal stem cells [37]. One of our previous papers described the efficiency of NSE to prevent neuroinflammation in the wild-type mice either treated with LPS of immunized with α7 nAChR extracellular domain 1-208 [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the stable and continuous pro-cognitive and anti-inflammatory effect of the agonist, the pro-cognitive effect of the type 2 PAM was transient and disappeared a week after the end of the injection cycle. Moreover, cessation of PNU120596 treatment resulted in a sharp increase of IL-1β and IL-6 levels in the blood of mice [ 142 ]. This result puts in doubt the idea of using type 2 PAMs instead of orthosteric α7 nAChR agonists for neuroprotection.…”
Section: Counteracting Aging Of Microgliamentioning
confidence: 99%
“…Due to their strategic location and enrichment in areas involved in working memory acquisition, maintenance, and retrieval, nAChRs in the hippocampus and cerebral cortex play major roles in cognition and mnemonic functions [ 19 , 20 ] and modulate prefrontal cortex functions involved in consciousness [ 21 ]. At present, we probably know only a fraction of the roles played by nAChR subtypes in the functioning of the human brain [ 22 ].…”
Section: Introductionmentioning
confidence: 99%